4‐Iodopyrimidine Labeling Reveals Nuclear Translocation and Nuclease Activity for Both MIF and MIF2. Issue 1 (22nd November 2021) - Xiao, Zhangping; Chen, Deng; Mulder, Fabian; Song, Shanshan; van der Wouden, Petra E.; Cool, Robbert H.; Melgert, Barbro N.; Poelarends, Gerrit J.; Dekker, Frank J.
Abstract: Macrophage migration inhibitory factor (MIF) and its homolog MIF2 (also known as D‐dopachrome tautomerase or DDT) play key roles in cell growth and immune responses. MIF and MIF2 expression is dysregulated in cancers and neurodegenerative diseases. Accurate and convenient detection of MIF and MIF2 will facilitate research on their roles in cancer and other diseases. Herein, we report the development and application of a 4‐iodopyrimidine based probe 8 for the selective labeling of MIF and MIF2. Probe 8 incorporates a fluorophore that allows in situ imaging of these two proteins. This enabled visualization of the translocation of MIF2 from the cytoplasm to the nucleus upon methylnitronitrosoguanidine stimulation of HeLa cells. This observation, combined with literature on nuclease activity for MIF, enabled the identification of nuclease activity for MIF2 on human genomic DNA. Abstract : Protein trafficking is an essential step for the functionalization of proteins. We report a 4‐iodopyrimidine based probe 8 for the selective labeling of MIF and MIF2. This enabled monitoring of the translocation of MIF2 from the cytoplasm to the nucleus upon methylnitronitrosoguanidine stimulation, which indicates a nuclease activity for MIF2 on human genomic DNA. Thus, we provide a tool for MIF and MIF2 localization study, as well as demonstrate a nuclease activity for MIF2.